2003
DOI: 10.2139/ssrn.908570
|View full text |Cite
|
Sign up to set email alerts
|

Do Homeowners Stay Unemployed Longer? A French Micro-Econometric Study

Abstract: L'objectif de cet article est une évaluation micro-économétrique de l'hypothèse d'Oswald selon laquelle la propriété immobilière produit des effets négatifs sur le marché du travail. On estime dans une première étape le choix du statut résidentiel par un modèle logistique multinomial. Les probabilités ainsi estimées d'être propriétaire, locataire ou logé à titre gratuit sont utilisées dans une seconde étape pour expliquer la durée des épisodes individuels de chômage. Cette méthode d'estimation flexible permet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
1
11
1
1
Order By: Relevance
“…The estimates of the MNL for housing tenure, as showed in Table , are also consistent with expectations and earlier evidence (Flatau et al., , ; Van Leuvensteijn and Koning, ; Battu et al., ; Brunet and Lesueur, ). In particular, the instruments are significant and have the expected signs.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The estimates of the MNL for housing tenure, as showed in Table , are also consistent with expectations and earlier evidence (Flatau et al., , ; Van Leuvensteijn and Koning, ; Battu et al., ; Brunet and Lesueur, ). In particular, the instruments are significant and have the expected signs.…”
Section: Resultssupporting
confidence: 89%
“…Several variables have been proposed in the literature to instrument housing tenure, or more specifically homeownership. One prominent instrument is the regional homeownership rate (Van Leuvensteijn and Koning, ; Munch et al., ; Brunet and Lesueur, ). However, this instrument has also been criticized for being likely related to labor market aggregate outcomes, hence likely to impact on individual performance (Coulson and Fisher, ; De Graaff, Leuvensteijn, and Van Ewijk, ; De Graaff and Van Leuvensteijn, ) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They followed individuals who entered unemployment and after controlling for selectivity bias concluded that 'unemployed individuals in owning households find jobs more rapidly than do unemployed individuals in renting households' (Green et al 2002, p. 18). Brunet and Lesueur (2003) found some support for the Oswald hypothesis in their analysis of French labour market and housing data. Ahn and Blazquez (2007) analysed data from Denmark, France and Spain, and concluded that Oswald's theory held only for Denmark and that the effect of home ownership on labour market mobility was insignificant in France and absent in Spain.…”
Section: Introductionmentioning
confidence: 93%